(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Drugs use and crimes have an intimate relationship. All the persons who use drugs are not criminals and all the criminals were not addicted to drugs. But addiction to drugs is directly related to the increase in normal and heinous crimes because of modified criminal behavior. Apart from crimes, drugs play a very effective role in communal, social, financial, and health disturbances and damages. Most of the countries have been facing problems with drugs use and crimes and are not free from drug trafficking and manufacturing. Many researchers and policymakers believe except only drug use leads to crime yet not crime lead to drug use. Drug abuse, as well as Narcotics, had led to a harmful impact on society. The types of drugs, ways of crimes, and their laws play important role in the administration for a better society.